The Environmental History of Colonial Mexico - Conway, Richard ca. 20./21. Jh. (History compass, 2017)
In spite of the sizable scholarly literature on New Spain, and notwithstanding the fact that environmental history is now a highly influential field, on first glance, there seem to be surprisingly few works of environmental history for colonial Mexico. Or are there? This article suggests that as a multi-disciplinary enterprise and as an area of history that overlaps and blends with many others, the environmental history of colonial Mexico has been far more abundant than a first glance might suggest. The blurring of the boundaries between disciplines and different kinds of history has become a hallmark of the scholarship in recent years. The adoption of methodological approaches from microhistory has become another. Together, these trends challenge our ideas about what it means to study environmental history even as they point us towards new opportunities for research.